2015
DOI: 10.1177/0363546515591266
|View full text |Cite
|
Sign up to set email alerts
|

Detrimental Effect of Repeated and Single Subacromial Corticosteroid Injections on the Intact and Injured Rotator Cuff

Abstract: The potential benefit and detrimental effects of corticosteroid injection should be thoroughly considered before it is administered subacromially in patients with RC injuries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
66
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(66 citation statements)
references
References 21 publications
(19 reference statements)
0
66
0
Order By: Relevance
“…Subacromial corticosteroid injections (CSI's) are a common non-surgical treatment for rotator cuff tears (RCT's) and other shoulder pathologies. While the science behind the use of CSI's is currently inconclusive [3][4][5][6][7][8][9][10] , they are typically employed along with other non-surgical measures like physical therapy, activity modification, and non-steroidal anti-inflammatory medications (NSAIDs), in order to reduce pain and increase functionality in patients with RCT's. When a combination of these therapies does not relieve patients' symptoms sufficiently, surgical repair is typically the next treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Subacromial corticosteroid injections (CSI's) are a common non-surgical treatment for rotator cuff tears (RCT's) and other shoulder pathologies. While the science behind the use of CSI's is currently inconclusive [3][4][5][6][7][8][9][10] , they are typically employed along with other non-surgical measures like physical therapy, activity modification, and non-steroidal anti-inflammatory medications (NSAIDs), in order to reduce pain and increase functionality in patients with RCT's. When a combination of these therapies does not relieve patients' symptoms sufficiently, surgical repair is typically the next treatment.…”
Section: Introductionmentioning
confidence: 99%
“…The results of several systematic reviews and meta-analyses over decades suggest there may be short-term symptomatic relief after CSI, but these results are often difficult to reproduce [4][5][6][7][8] . In addition, case reports from the past have suggested a correlation of CSI and tendon rupture [19][20][21] , which has been confirmed in multiple animal models 6,9,10,22 . Previous studies have also shown an increase in post-operative infection rates in patients who received pre-or peri-operative CSI's [23][24][25] , but recent systematic reviews and meta-analyses have challenged these claims 11,13,26,28 .…”
Section: Discussionmentioning
confidence: 77%
“…Concerns about a local corticosteroid injection for tendinopathy arise from its potential side effects, including tendon degeneration, the weakening of the injected tendon, decreasing biomechanical strength at the injected site, and ruptures [16][17][18][19][20][21][22][23]. Intra-articular treatment with corticosteroids also increases apoptosis in human rotator cuff tears and the tendency was similar in all rupture sites [24].…”
Section: Discussionmentioning
confidence: 99%